The Level of Mass Media Usage in Cattle Extension Communication Network - Amiruddin Saleh (Universitas Trisakti, 2010)
This research aim were: (1) To recognize the communication behavior of cattle farmers in searching information, (2) To analyze the level of farmer participation in cattle farmer communication network, (3) To explore the relationship between individual characteristics, (4) To explore interpersonal communication behavior and mass media utilization in cattle farmer communication network. The results showed that: (1) There was a significant difference of communication behavior between the advanced cattle farmers group and the less advanced one. This result informed the distinction of mass media used by cattle farmers in searching information i.e. interpersonal communication relationship in receiving and diffusing information and impersonal communication (media communication) behavior, particularly from television, broadcast and newspapers. (2) There was a significant relationship between formal education characteristic and impersonal communication behavior (television and radio and newspaper). There were significant relationship between economic class and newspaper impact behavior, between mass media ownership and television impact behavior, between education level and mass media ownership with the information search behavior. Individual characteristics of advanced farmers group have negative correlation with the information distribution behavior. Advanced farmer group were characterized by: well educated, higher economic class, more variety of mass media ownership, have more capability to select information according to their needs, profit oriented, risk taker, cosmopolites, have a communication pattern and good relationship among cattle farmer group. All of those characteristics caused un-proper of information diffusion